Pengaruh Biaya Periklanan Terhadap Pendapatan Usaha Pada CV. Excel Agency Di BSD City Tangerang Selatan - Dina Iksani; Darwin Erhandy (ITB Ahmad Dahlan Jakarta, 2019)
This study purposes to analyze the effect advertising costs on business income on in CV Excel Agency. CV Excel Agency is a company engaged in advertising, especially in the distribution of brochures and advertising through various other print media. This study uses a quantitative associative analysis method with software for managing data, namely SPSS. This research was conducted to find out how the relationship that occurs in advertising costs on business income, whether there are positive or negative influences. This study uses secondary data obtained from financial statements on advertising costs and CV Excel Agency's operating income for 5 (five) years in the period 2013-2015. The results of testing this study will be discussed further in this article.